Evaluation of the care line in the care of users with sti’s in a center of testing and advice - Lirio Sotero, Rafaela; Guimarães, Nilo Plantiko; Scabelo Galavote, Heletícia (Guará Journal, 2017)
The testing and counseling centers (TACs) offer free, confidential and anonymous testing, with an emphasis on practicing action planning counseling by identifying vulnerabilities. Thus, the present study aims to evaluate the care line, in the care of users with HIV/AIDS in a CTA. This is a descriptive study of a qualitative approach carried out in the CTA, in a municipality of the state of Espírito Santo, using as data collection instruments the descriptor flowchart as an analyzing tool for the production of the care line. The results demonstrate an organization of the work process that differs from that based on ministerial protocols. It is concluded that the use of analytical tools of the work process allowed to unveil the organization of the service focusing on the existing critical nodes, for the production of a care line in the user-centered format.